Ammonia plasma treatment of polystyrene surfaces enhances proliferation of primary human mesenchymal stem cells and human endothelial cells. Issue 3 (9th November 2012) - Kleinhans, Claudia; Barz, Jakob; Wurster, Simone; Willig, Marleen; Oehr, Christian; Müller, Michael; Walles, Heike; Hirth, Thomas; Kluger, Petra J.
Abstract The control of surface properties is a substantial step in the development and improvement of biomaterials for clinical applications as well as for their use in tissue engineering. Interaction of the substrate surface with the biochemical or biological environment is crucial for the outcome of the applied biomaterial and therefore should meet specific requirements regarding the chemical composition, wettability, elasticity, and charge. In this study, we examined the effect of chemical groups introduced by low pressure plasma treatments of polystyrene surfaces on the cell behavior of primary human mesenchymal stem cells (hMSCs) and dermal microvascular endothelial cells (hDMECs). X‐ray photoelectron spectroscopy analysis and contact angle measurements were employed to evaluate ammonia‐, carbon dioxide‐, and acrylic acid‐plasma modifications to substrate surfaces. HMSCs and hDMECs were analyzed simultaneously to identify the most suitable surface functionalization for each cell type. Significantly higher cell proliferation was detected on ammonia plasma‐treated surfaces. Cell‐material interaction could be shown on all created interfaces as well as the expression of typical cell markers. Hence, the applied plasma treatment presents a suitable tool to improve culture condition on polystyrene for two important cell types (hMSCs and hDMECs) in the field of tissue engineering.